Analysis of green tourism development potential in tourist destinations in Garut Regency - Dani Adiatma; Deden Firman Syuyaman Rukma; Stanny Dhamayanti (Journal of Applied Sciences in Travel and Hospitality, 2025)
Although interest in green tourism in Indonesia continues to increase, evidence at the district level, especially in secondary destinations, is still limited. Most previous research has focused on primary destinations such as Bali and Yogyakarta, while evidence-based studies in areas such as Garut are still rare. This study offers a novelty by analysing the potential, opportunities, and challenges of green tourism development in Garut Regency through a descriptive-qualitative approach and SWOT framework based on secondary data. Garut has an authorised capital in the form of 12 main destinations, ranging from volcanic landscapes (Mount Papandayan), lakes (Situ Bagendit), the south coast, to cultural heritage (Cangkuang Temple and leather crafts Sukaregang). However, data from DLH Garut shows that the scope of waste management has only reached 17%, which confirms the gap between potential and implementation in the field. The findings of this study identify four main challenges: (I) Poor Solid Waste Management, (ii) lack of measurable targets for water and energy conservation, (iii) uneven supporting infrastructure, and (iv) low community participation. This study provides a real contribution to local governments in formulating environmental policies and sustainable tourism, for tourism actors to adopt environmentally friendly practices and green certification, and for academic literature as a reference for the development of green tourism in secondary destinations in Indonesia.